Foliar Fertilization on BRRI dhan28 To Reduce Soil Application of Nitrogenous Fertilizer - Mohona, M A J; Hasan, M A; Chowdhury, A K M M B; Hafiz, M H R; Islam, M R; Sharmin, S (Bangladesh Agronomy Journal, 2024)
The experiment was conducted at the research farm of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur during November 2019 to June 2020 to find out the effect of foliar fertilization on the performance of rice var. BRRI dhan28 and to estimate how much nitrogenous fertilizer can be saved by foliar fertilization without yield reduction. The experiment was laid out following split plot design with three replications. Four levels of foliar fertilization (F0 – No foliar fertilization, F1 – Foliar fertilization with 2% KNO3, F2 - Foliar fertilization with 2% DAP and F3 - Foliar fertilization with 1% American NPKS) were placed in the main plot treatments whereas three nitrogen fertilizer levels (N50 -50% of the recommended nitrogen fertilizer, N75 – 75% of the recommended nitrogen fertilizer and N100 – 100% of the recommended nitrogen fertilizer) were placed randomly in the sub-plots. Foliar fertilization with KNO3, DAP (Di-ammonium phosphate) and American NPKS significantly increased the grain yield (t ha−1) compare to control (F0) but KNO3 and American NPKS performed better than DAP. Foliar fertilization with KNO3 and American NPKS could save 25% of recommended nitrogen fertilizer but foliar fertilization with DAP could not save nitrogen fertilizer applied in soil for getting comparable grain yield found in F0N100. Foliar fertilization of KNO3 and American NPKS with recommended nitrogen fertilizer applied in soil could increase 11.8 and 12.5% grain yield, respectively compare to F0N100. Bangladesh Agron. J. 2024, 26(2): 77-85